A review of current theories and treatments for phantom limb pain - Collins, Kassondra L. (J Clin Invest, 2018)
Following amputation, most amputees still report feeling the missing limb and often describe these feelings as excruciatingly painful. Phantom limb sensations (PLS) are useful while controlling a prosthesis; however, phantom limb pain (PLP) is a debilitating condition that drastically hinders quality of life. Although such experiences have been reported since the early 16th century, the etiology remains unknown. Debate continues regarding the roles of the central and peripheral nervous systems. Currently, the most posited mechanistic theories rely on neuronal network reorganization; however, greater consideration should be given to the role of the dorsal root ganglion within the peripheral nervous system. This Review provides an overview of the proposed mechanistic theories as well as an overview of various treatments for PLP.